2012
DOI: 10.1111/j.1471-1842.2011.00975.x
|View full text |Cite
|
Sign up to set email alerts
|

Calling All Students!!!

Abstract: Abstract'Dissertations into Practice' is a new regular feature in the Health Information and Libraries Journal, which aims to encourage students to write for publication. The idea is that students will write an extended abstract of their health-related dissertations, outlining the methods used and commenting on the implications for practice. Co-written with their dissertation or workplace supervisor, this feature will provide a safe environment for students to see their writing in print, possibly for the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…In the first article, in which I introduced the feature, I referred to the research gap in the library and information world, often conceptualised as a tension between academics and practitioners. 1 In an update article in September 2015, 2 I suggested that this research gap was a continuing feature in our profession and that 'many information practitioners feel daunted by the idea of carrying out research, and lack the confidence needed to become involved in research activities'. 3 However, as I also pointed out, many practitioners are in fact conducting research without realising itcollecting and analysing data or evaluating an aspect of a serviceand small research projects such as those can be of value to a wider audience than the service's host organisation.…”
Section: Audrey Marshallmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first article, in which I introduced the feature, I referred to the research gap in the library and information world, often conceptualised as a tension between academics and practitioners. 1 In an update article in September 2015, 2 I suggested that this research gap was a continuing feature in our profession and that 'many information practitioners feel daunted by the idea of carrying out research, and lack the confidence needed to become involved in research activities'. 3 However, as I also pointed out, many practitioners are in fact conducting research without realising itcollecting and analysing data or evaluating an aspect of a serviceand small research projects such as those can be of value to a wider audience than the service's host organisation.…”
Section: Audrey Marshallmentioning
confidence: 99%
“…In the first article, in which I introduced the feature, I referred to the research gap in the library and information world, often conceptualised as a tension between academics and practitioners . In an update article in September 2015, I suggested that this research gap was a continuing feature in our profession and that ‘many information practitioners feel daunted by the idea of carrying out research, and lack the confidence needed to become involved in research activities’ .…”
Section: Introductionmentioning
confidence: 99%
“…In this month’s issue we seek to address this research/practice gap with the introduction of a new feature specifically tasked with seeking to encourage students to close the research loop and engage in disseminating their project findings. Edited by Audrey Marshall, 5 Dissertations into Practice will provide a safe and structured environment for students, be it at undergraduate, postgraduate or PhD level, to summarise their research findings, describe their research methods and illustrate how the implications of their study could inform practice. Further details can be found towards the end of this issue 5 …”
mentioning
confidence: 99%
“…Edited by Audrey Marshall, 5 Dissertations into Practice will provide a safe and structured environment for students, be it at undergraduate, postgraduate or PhD level, to summarise their research findings, describe their research methods and illustrate how the implications of their study could inform practice. Further details can be found towards the end of this issue 5 …”
mentioning
confidence: 99%
“…Our Learning and Teaching in Action Editor Hannah Spring looks at the theories of learning, and specifically models of good practice for evidence‐based information skills teaching, again focusing on this key area for the health library and information professional . Finally, we introduce our new regular feature Dissertations into Practice , which calls for information studies students to submit their research to the journal, engaging with the next generation of health library and information professionals …”
mentioning
confidence: 99%